2011
DOI: 10.1002/jsfa.4551
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance reversal effect of DMC derived from buds of Cleistocalyx operculatus in human hepatocellular tumor xenograft model

Abstract: All results suggested that DMC reverses 5-FU resistance, with a benign side effects profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 139 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…We found that tumor inhibition rate was 31.51%, 43.79%, and 76.29% in the B, C, and D groups, respectively. We tested if the ACNU and HBOT combination showed synergism based on Jin's formula Q = Ea + b/(Ea + Eb – Ea × Eb), where Ea + b, Ea, and Eb are the average effects of the combination treatment, and Q < 0.85 indicates antagonism, 0.85 ≤ Q < 1.15 indicates additivity, and Q ≥ 1.15 indicates synergism . Our Q value was 1.24, indicating ACNU, and combination treatment showed synergistic effect.…”
Section: Resultsmentioning
confidence: 99%
“…We found that tumor inhibition rate was 31.51%, 43.79%, and 76.29% in the B, C, and D groups, respectively. We tested if the ACNU and HBOT combination showed synergism based on Jin's formula Q = Ea + b/(Ea + Eb – Ea × Eb), where Ea + b, Ea, and Eb are the average effects of the combination treatment, and Q < 0.85 indicates antagonism, 0.85 ≤ Q < 1.15 indicates additivity, and Q ≥ 1.15 indicates synergism . Our Q value was 1.24, indicating ACNU, and combination treatment showed synergistic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The compound DMC has been isolated from C. operculatus [7], M. serrata [8], and S. samarangense [9]. DMC possessed hepatoprotective [10], cytoprotective [11], anti-inflammatory [12], antifungal, antibacterial [8], anti-TB [13], antiviral [14], antispasmodic [15], antidiarrhoeal [16], antihyperglycaemic [17], anti-MDR [18, 19], and antiapoptotic effect [20]. DMC has been evaluated for its cytotoxic activity on various human cancer cells including liver cancer (SMMC-7721s), HeLa (SPC-A-1, 95-D, and GBC-SD) [7], colon (SW-480) [9], leukemia (K562) [21], colorectal carcinoma (HCT-116 and LOVO) [22], breast (MDA-MB-453), and ovarian [23] cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer surgery can cause many side effects such as weight loss, fatigue, sickness and loss of appetite depending on the invaded location and size. Several natural products, such as epigallocatechin gallate (EGCG) [ 23 ], 2′,4′-Dihydroxy-6′-methoxy-3′,5′-dimethylchalcone [ 24 ], hyperforin and nemorosone [ 25 ], Daickenchuto [ 26 , 27 ] and so forth were reported to be effective against these side effects ( Table 1 ). Stingl et al suggested that epigallocatechin gallate (EGCG) extracted from green tea minimized the risk of metachronous adenomas of the colorectum with colorectal polyp removal surgery [ 23 ].…”
Section: Sequela Of Surgery and Plant Extractsmentioning
confidence: 99%